APPLICATION OF MODEL EMPIRICAL INDUCTIVE LEARNING CYCLE TO INCREASE STUDENT KNOWLEDGE AND ABILITY MATHEMATICAL REASONING IN JUNIOR HIGH SCHOOL - Kurniasih, Eka Rachma (2013)
The research is based on the problems and lack of understanding of mathematical reasoning ability junior high school students in math. The research aims to assess the improvement of understanding and mathematical reasoning skills among students who obtain empirical inductive learning cycle model and conventional learning. This research was a quasi-experimental design with non-equivalent control group using purposive sampling technique, students take one research subject in Junior High School Pangkalpinang Bangka Belitung Islands Province. While the study sample is grade students experiment with the number 50 and the number of control grade 51. The instrument used was a test comprehension and mathematical reasoning abilities, student observation sheet. Quantitative analysis performed using the mean difference test and two ways ANOVA test. The results showed, (1) Improved understanding and mathematical reasoning ability junior high school students get lesson in empirical inductive learning cycle model better than students who received conventional learning, (2) There is interaction between the models (empirical inductive learning cycle and conventional) and knowledge early mathematical (top and bottom) in improving students' understanding of students' mathematical ability, (3) There is no interaction between the models (empirical inductive learning cycle and conventional) and early mathematical knowledge (top and bottom) in improving students' mathematical reasoning abilities of students, (4 ) Activities of students during the learning cycle empirical inductive learning is high and very high. Penelitian ini didasarkan pada permasalahan rendahnya kemampuan pemahaman dan penalaran matematis siswa SMP dalam pelajaran matematika. Penelitian bertujuan mengkaji peningkatan kemampuan pemahaman dan penalaran matematis antara siswa yang memperoleh model siklus belajar empiris induktif dan pembelajaran konvensional. Penelitian ini merupakan penelitian kuasi eksperimen dengan desain kelompok control non-equivalent menggunakan teknik Purposive Sampling dengan mengambil subjek penelitian adalah siswa salah satu SMP Negeri di Kota Pangkalpinang Provinsi Kepulauan Bangka Belitung. Sedangkan sampel penelitiannya adalah siswa kelas eksperimen dengan jumlah 50 dan siswa kelas kontrol dengan jumlah 51. Instrumen yang digunakan adalah tes pengetahuan awal matematis, tes kemampuan pemahaman dan penalaran, lembar observasi siswa. Analisis kuantitatif dilakukan dengan menggunakan uji perbedaan rerata dan uji Anova dua jalur. Hasil penelitian menunjukkan, (1) Peningkatan kemampuan pemahaman dan penalaran matematis siswa SMP yang mendapatkan pembelajaran dengan model siklus belajar empiris induktif lebih baik daripada siswa yang mendapatkan pembelajaran konvensional; (2) Terdapat interaksi antara model (siklus belajar empiris induktif dan konvensional) dan pengetahuan awal matematis (atas dan bawah) siswa dalam peningkatan kemampuan pemahaman matematis siswa; (3) Tidak terdapat interaksi antara model (siklus belajar empiris induktif dan konvensional) dan pengetahuan awal matematis (atas dan bawah) siswa dalam peningkatan kemampuan penalaran matematis siswa; (4) Aktivitas siswa selama pembelajaran siklus belajar empiris induktif tergolong tinggi dan sangat tinggi. Kata kunci: model siklus belajar empiris induktif, kemampuan pemahaman, penalaran matematis